Corporate governance, business ethics, risk management and internal control - Cabrera, Ma. Elenita Balatbat; Cabrera, Gilbert Anthony; Cabrera, Bernadette Ann B. (Manila : GIC Enterprises & Co., Inc., 2021)
The business environment continues to change in dramatic ways and university graduates joining the corporate world or entering the accountancy profession, whether it be in public practice sector, management accounting practice, internal audit or accounting information system management must be prepared for a high standards of responsibility. This textbook on corporate governance, business ethics, risk management and internal control aims to equip its readers the basic knowledge skill and perspective that are necessary in facing this challenge.
1. Introduction to corporate governance -- 2. Corporate governance responsibilities and accountabilities -- 3. Securities and exchange commission code of corporate governance -- 4. Sec code of corporate governance, continued -- 5. Introduction to ethics -- 6. Business ethics -- 7. Common unethical practices of business establishments -- 8. Ethical dilemma -- 9. Advocacy against corruption -- 10. Initiatives to improve business ethics and reduce corruption -- 11. Risk management -- 12. Practical insights in reducing and managing business risks -- 13. Overview of internal control -- 14. Fraud and error -- 15. Errors and irregularities in the transaction cycles of the business entity -- 16. Internal control affecting assets -- 17. Internal control affecting liabilities and equity -- Appendices -- References.
Includes bibliographical references.
Keywords: CORPORATE GOVERNANCE